Peningkatan Hasil Belajar Matematika Melalui Pendekatan Matematika Realistik Pada Operasi Hitung Di Kelas II SDN 16 Sungai Sirah Kecamatan Pariaman Timur Kota Pariaman - Jasnimar Jasnimar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Mathematics learning for grade II of elementary students used to separate between learning and real life. This research is aimed to improve learning output of students by implementing realistic mathematics approach in mathematics learning. This is a class action research that consists of two cycles including four steps: planning, action, observation, and reflection. Subject of this research are 25 elementary students grade II SDN 11 Sungai Sirah Kecamatan Pariaman Timur Kota Pariaman. Data of research were obtained through observation, interview, and test. Obtained data were analyzed quantitatively and qualitatively. Learning output of students is improved in each cycle. In cycle I, average score of students’ learning output is 77.2. Meanwhile in cycle II, average score of students’ learning output is 88.2. Hence, it can be concluded that mathematics learning implementing realistic mathematics approach can improve the learning output of elementary students grade II.